Impact of Problem-Based Learning (PBL) on Knowledge Retention and Clinical Reasoning: A Systematic Review: Impact of PBL on Knowledge Retention and Clinical Reasoning - Waqar, Hanzala; Ali, Waqas; Faryal, Uzma; Fatima, Sadia; Hassan, Bilqis; Jalal, Sammer Fatima (Pakistan Journal of Health Sciences, 2025)
Problem-Based Learning (PBL) is a learner-centered educational approach widely adopted in health professions education to enhance critical thinking, self-directed learning, and long-term knowledge retention. However, results from individual studies vary, warranting a synthesis of recent evidence. Objectives: To evaluate studies published between 2019 and 2024 to determine the impact of PBL on knowledge retention and clinical reasoning among medical, nursing, dental, and allied health students. Methods: This systematic review followed PRISMA 2020 guidelines. PubMed, ScienceDirect, ERIC, and Google Scholar were searched (January 2019–December 2024) using MeSH terms and Boolean operators. Eligible studies included quasi-experimental, cross-sectional, survey-based, and observational designs measuring knowledge retention or clinical reasoning. Two reviewers independently screened and extracted data, resolving disagreements by consensus. Due to heterogeneity, a narrative synthesis was performed, summarizing p-values, effect sizes, and confidence intervals. Risk of bias was assessed across six domains. Results: Fourteen studies met the inclusion criteria. Most reported significant improvements in knowledge retention (t (76) = 3.93, p=0.00, β=9.40, p=0.03) and clinical reasoning (t=-4.599, p<0.001) with PBL compared to lectures. A few studies showed no significant difference, though student preference favored PBL. Performance and reporting biases were low, with some studies showing unclear selection and detection bias. Conclusions: PBL consistently improves knowledge retention and clinical reasoning across health professions education. Despite methodological variability, the evidence supports integrating PBL into curricula. Future research should adopt standardized outcome measures and rigorous study designs to strengthen the evidence base.